To what extent does South Africa s legal framework effectively combat child trafficking and comply with international law obligations? - Ertekin, Nesrin (Department of Public Law, 2025)
This thesis conducts a comprehensive critical analysis of South Africa's legislative and policy measures aimed at combatting child trafficking. It commences by presenting and critically examining the international definition of trafficking arising from the Palermo Protocol while also investigating the causes of trafficking. Subsequently, it delves into identifying and exploring South Africa's legal obligations, especially concerning children, as outlined in international and regional treaties. These obligations encompass a multifaceted commitment, including the duty to prevent trafficking, prosecute offenders, and ensure the protection of trafficking victims. Building upon this framework, the thesis critically evaluates South Africa's legal response primarily focusing on the Prevention and Combating of Trafficking in Persons (TIP) Act (7 of 2013) in light of these obligations. Furthermore, it assesses the implementation and effectiveness of the TIP Act. Ultimately, the thesis reaches a nuanced conclusion. It acknowledges that despite some deficiencies in the TIP Act, particularly regarding child trafficking, the legislation predominantly aligns with international and regional standards. However, its effectiveness is hindered by shortcomings in implementation, significantly undermining the TIP Act's potential to combat trafficking comprehensively. In conclusion, the thesis presents recommendations aimed at more effectively combating child trafficking.